PENYUSUNAN DOKUMEN POTENSI BAHAN TAMBANG DI LUAR WILAYAH SUNGAI KABUPATEN PEKALONGAN - Najib Najib (TEKNIK, 2010)
Besides in River area, Pekalongan Regency estimated has mineral potential in some areas outside of that area.Yet local government doesn’t have data about the potency of that mineral. In consequence, it is needed toconducts mapping of mineral potency outside of river circumstance that the result will be used by localgovernment either guide taking policy in exploitation or regulation to that activity. This research used somesteps i.e. measurement and mapping phase, analysis and data processing (hypothetic reserve calculation andlaboratory mineral tests such as AAS, petrography and shear strength) and data compilation. The potency ofminerals and rocks is disseminated in 14 districts in Pekalongan Regency. Types of those mine materials areAndesite, Diorite, Limestone, Tras, Clay, Ochre, Gold and iron sand. Mining systems possibly conducted are PitType System, Eunuch Hill System and Cave System.